2008
DOI: 10.1158/0008-5472.can-08-0442
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Activation of Androgen Receptor in a New Neuropeptide-Autocrine Model of Androgen-Insensitive Prostate Cancer

Abstract: Treatment of advanced prostate cancer with androgen deprivation therapy inevitably renders the tumors castration-resistant and incurable. Under these conditions, neuroendocrine differentiation of prostate cancer (CaP) cells is often detected and neuropeptides released by these cells may facilitate the development of androgen independence. Exemplified by gastrin-releasing peptide (GRP), these neuropeptides transmit their signals through G protein-coupled receptors, which are often overexpressed in prostate canc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 51 publications
6
47
0
1
Order By: Relevance
“…4 These findings strongly indicate that the GRPR can mediate cancer initiation and growth by modulating AR signalling, even in the absence of androgen stimulation. Thus, the GRPR is a particularly promising target for the inhibition of tumour progression in patients with castration-resistant prostate cancer.…”
Section: Rafael Roesler and Gilberto Schwartsmannmentioning
confidence: 86%
“…4 These findings strongly indicate that the GRPR can mediate cancer initiation and growth by modulating AR signalling, even in the absence of androgen stimulation. Thus, the GRPR is a particularly promising target for the inhibition of tumour progression in patients with castration-resistant prostate cancer.…”
Section: Rafael Roesler and Gilberto Schwartsmannmentioning
confidence: 86%
“…New therapeutic strategies such as small-molecule inhibitors of signaling pathways responsible for cancer progression are desirable. Src kinase has been implicated in prostate tumor proliferation, migration, survival (23,35,36), and progression to castration resistance (26). Many recently developed small-molecule SFK inhibitors, including bosutinib (SKI-606; ref.…”
Section: Discussionmentioning
confidence: 99%
“…38,39), and saracatinib are able to reduce the proliferation, migration, and invasion of prostate cancer cell lines in vitro and are currently in clinical trials. These inhibitors also decrease prostate cancer growth and metastasis in mouse xenograft studies (26,29,39). Recent studies using saracatinib showed that Src has a pivotal role in the formation and activation of human osteoclasts (40) and is involved in breast cancer bone metastasis regardless of the estrogen receptor status (41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations